Analysis of Spiritual Intelligence and Organizational Commitment to Employee Performance with Organizational Citizenship Behavior (OCB) as Intervening Variables In BMT Amanah Ummah Sukoharjo - Tho'in Muhammad; Siti Sulistiani; Iin Emy Prastiwi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to determine the effect of spiritual intelligence, organizational commitment on employee performance with organization citizenship behavior (OCB) as an intervening variable at BMT Amanah Ummah Sukoharjo. This study uses a quantitative approach with a population of BMT Amanah Ummah Sukoharjo employees, the sample used in this study was 57 respondents using PLS. The results of the study stated that spiritual intelligence had a positive and significant effect on employee performance. Spiritual intelligence variable has a positive and significant effect on organizational citizenship behavior (OCB). Organizational commitment variable does not have a positive and significant effect on employee performance. The organizational commitment variable does not have a positive and significant effect on organizational citizenship behavior (OCB).Variable organizational citizenship behavior (OCB) has a positive and significant effect on employee performance. Variable organizational citizenship behavior (OCB) is able to mediate the influence of spiritual intelligence on employee performance. Variable organizational citizenship behavior (OCB) is not able to mediate the effect of organizational commitment on employee performance.